Myelin Oligodendrocyte Glycoprotein Antibody Associated Cerebral Cortical Encephalitis: Case Reports and Review of Literature - Shu, Hang; Ding, Manqiu; Shang, Pei; Song, Jia; Lang, Yue; Cui, Li (Frontiers in Human Neuroscience, 2022)
Myelin oligodendrocyte glycoprotein antibody-associated disease is an immune-mediated demyelinating disease of the central nervous system that is present in both adults and children. The most common clinical manifestations are optic neuritis, myelitis, acute disseminated encephalomyelitis, and brainstem syndrome. Cerebral cortical encephalitis (CCE) is a rare clinical phenotype of myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD), which usually begins with seizures, headaches, and fever, and may be misdiagnosed as viral encephalitis in the early stages. Herein, we report two typical MOG antibody (MOG-Ab)-positive patients presenting with CCE, both of whom presented with headache, fever, seizures, and who recovered completely after immunotherapy. In addition, we performed a systematic review of the present literature from the perspectives of population characteristics, clinical symptoms, MRI abnormalities, treatments, and prognosis. Among the patients reported in 25 articles, 33 met our inclusion criteria, with the age of onset ranging from 4 to 52 years. Most of the patients had seizures, headache, fever, and unilateral cortical lesions on brain MRI. For acute CCE, 30 patients were treated with high-dose intravenous methylprednisolone, and the symptoms of most patients were completely relieved after immunotherapy. This study reported our experience and lessons learned in the diagnosis and treatment of MOG-Ab-positive CCE and provides a systematic review of the literature to analyse this rare clinical phenotype.